Electric Welding Vocational Training for Youth in Entrepreneurship - Anugrah, Despiantini; Musa, Syafiri; Hidayat, Dayat (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2021)
Despiantini (1610631040010). Vocational training of electric welding for youth in Entrepreneurial Training Hall (BLK) Kab. Purwakarta. School of Education Study Program, Faculty of Teacher Training and Education Sciences, University of Singaperbangsa Karawang, 2020.The background of this study was the many unemployment that existed in Kab. Purwakarta which is mainly from the youth circles, and lack of skills among others in electric welding so lost to compete in the workforce. Thus the problem formulation of this research is how the implementation and results of vocational training of electric welding for the youth in entrepreneurship at the Training Hall (BLK) Kab. Purwakarta. The purpose of this research is to obtain an overview of the implementation and outcome of vocational training of electric welding for the youth in Entrepreneurship at the Kab work Training Hall. Purwakarta. The foundations of the theory used in this research include the concept of training. Training is a process of educative interaction between citizens studying with the training components. The training components include: raw input (raw input), instrumental input (input), environmental input, process, output (output), other input, and outcome (influence)... This study used a qualitative approach with a case study method conducted at Kab Training Hall (BLK). Purwakarta. The number of research subjects was five respondents, one organizer, an instructor, and three people. The data collection techniques used in this study are observations, interviews, and documentation analysis. The stages involved in this training include the orientation stage, the exploration stage, and the member check stage.The results of the study as follows: (1) Kab Working Training Hall (BLK). Purwakarta has been conducting vocational training for electrical welding through planning, implementation, and assessment of 28 days of training @ 10 hours lessons/day with 16 people who study trained by one person instructor, and (2) District Training Hall (BLK). Purwakarta has trained 16 people of citizens learn in the mastery of SMAW 2G welding skills in accordance with the prevailing standards. Advice on the implementation of electrical welding vocational training among others so that the BLK can be equipped with electric tools that are still lacking.Keywords: training, welding electricity, entrepreneurship